Ni-YSZ cermet anode fabricated from NiO-YSZ composite powder for high-performance and durability of solid oxide fuel cells - Kim, Sun-Dong; Moon, Hwan; Hyun, Sang-Hoon; Moon, Jooho; Kim, Joosun; Lee, Hae-Weon (ELSEVIER SCIENCE BV, 2007)
A functional composite powder, in which Dano-sized NiO (40 vol.%) was crystallized on YSZ particles, was synthesized by the Pechini-type polymerizable complex method in an effort to improve the performance and durability of SOFC anodes. The pore-structure (e.g. porosity, pore size) and mechanical properties (e.g. strength, density) of the electrode were optimized by a combination of two different species of YSZ powder (Tosoh 0.3 mu m and Millennium 10 mu m). A single cell made from the composite powder exhibited high power density of 1.1 W cm(-2) and high durability under a load of 1.0 A cm(-2) during 530 h of operating time at 800 degrees C. It could be concluded that this functional composite would enhance the single cell performance and durability at elevated temperature. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: SINTERING BEHAVIOR; NI/YSZ CERMET; SOFC; MICROSTRUCTURE; DEGRADATION; ELECTRODES